Factors Related to Waste Management Behavior in Housewives in Masangau Hamlet, Silau Padang, Sipispis, Serdang Bedagai - Nanda, Meutia; Safira, Putri; Amrainum, Desri; Sianturi, Anggina Cucu Ketri; Humaira, Annisa (PROMOTOR, 2024)
Waste management in households is very important in the context of environmental and community sustainability because household waste is still the main contributor to waste. The active role and participation of the community, especially housewives, is needed to reduce the amount of waste sent to landfill, waste sorting practices and grouping them in different containers according to their type. The purpose of the study was to determine the factors related to waste management behavior in housewives in Masangau Hamlet, Silau Padang, Sipispis, Serdang Bedagai. This study is a quantitative study using a cross-sectional design. The study population consisted of 85 housewives in Masangau Hamlet. A sample of 45 respondents was selected using the Simple Random Sampling method based on the Lemeshow formula. Data analysis was performed with chi-square tests for univariate and bivariate analysis, using questionnaires as instruments. The results showed that the majority of respondents were aged 25-59 years (84.4%), with 6.7% over 60 years old. A total of 57.8% had higher education and 42.2% had low education. Most (73.3%) work as housewives. The respondents' knowledge was divided into 55.6% good and 44.4% low, while the attitude was 66.7% good and 33.3% less good. Only 22.2% had good facilities, and 77.8% were not good. High motivation was recorded in 46.7% of respondents, and 53.3% had low motivation. Waste management behavior was good by 44.4%, and 55.6% was not good. The chi-square test showed p-values of 0.627 for age and 0.177 for occupation, both >0.05, showing no significant association. However, there is a significant relationship between waste management behavior with education (p-value 0.017), knowledge (p-value 0.001), attitude (p-value 0.001), facilities and infrastructure (p-value 0.014), and motivation (p-value 0.002). In conclusion, there is a relationship between education, knowledge, attitudes, facilities and infrastructure, and motivation with waste management behavior, but no relationship with age and occupation.